The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.2478/abcsb-2013-00015
|View full text |Cite
|
Sign up to set email alerts
|

Natural Hybrid Zone of Aconitum Species in the Western Carpathians: Linnaean Taxonomy and ISSR Fingerprinting

Abstract: Aconitum lasiocarpum (Carpathian endemic) and A. variegatum (European endemic) occur sympatrically in the Polish Western Carpathians. Here their taxonomic hybrid A. ×pawlowskii occurs. The aim of this study was to determine the relationship between the taxonomic (Linnaean approach) and genetic structure (PCR-ISSR analysis) of the populations and individuals in two allopatric and four sympatric populations. We determined 309 individuals (OTUs) to species, subspecies and nothospecies using the Linnaean system of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 52 publications
(40 reference statements)
2
16
0
Order By: Relevance
“…in Salix (Hardig et al, 2000) and Tilia (Fromm, 2003). Such hybrid complexes are also found in Aconitum (Sutkowska et al, 2013) and, using Linnaean taxonomy, are given the status of nothotaxa (Mitka, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…in Salix (Hardig et al, 2000) and Tilia (Fromm, 2003). Such hybrid complexes are also found in Aconitum (Sutkowska et al, 2013) and, using Linnaean taxonomy, are given the status of nothotaxa (Mitka, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…We recognized a putative hybrid zone B. ramosus and B. benekenii in northern France during our previous studies (Sutkowska et al, 2013). It is formed by two polyploid species of hybridogenous origin: allotetraploid Bromus benekenii and allohexaploid B. ramosus.…”
Section: Introductionmentioning
confidence: 99%
“…This cryptic introgression, i.e. the genetic change not accompanied by any morphological-taxonomic traits, could be a sign of secondary contact influencing the pattern [3,12]. Aconitum plicatum is genetically richer and have the greatest number of unique AFLP bands species.…”
Section: Gene Pool Of Aconitum Plicatum In the Carpathian Taxamentioning
confidence: 99%
“…In Aconitum the cryptic introgression, i.e. the admixture of alien genes not accompanied by the morphological changes, was to be found [12]. The hypothesis on gene flow between the Sudetic and Carpathian Aconitum is assessed by testing relationships between the genetic and taxonomic structure of the populations.…”
Section: Introductionmentioning
confidence: 99%
“…The ISSR was also successfully employed to assess hybridization and detect hybrid taxa (e.g. Wolfe et al, 1998;Conte et al, 2007;Goldman, 2008;Kramina et al, 2012;Sutkowska et al, 2013). Many studies have demonstrated the efficacy of those markers, both in the phylogenetic analyses and taxonomic relationships of Allium species (Hao et al, 2002;Son et al, 2012) as well as in population and cultivar genetics studies (Hur et al, 2006;Jabbes et al, 2011).…”
Section: Introductionmentioning
confidence: 99%